HLA allele and haplotype frequencies of registered stem cell donors in Chile - Solloch, Ute V.; Giani, Anette S.; Pattillo Garnham, Maria Ignacia; Sauter, Jürgen; Bernas, Stefanie N.; Lange, Vinzenz; Barriga, Francisco; Fernández-Viña, Marcelo A.; Schmidt, Alexander H. (Frontiers in Immunology, 2023)
Patients in need of hematopoietic stem cell transplantation often rely on unrelated stem cell donors matched in certain human leukocyte antigen (HLA) genes. Donor search is complicated by the extensive allelic variability of the HLA system. Therefore, large registries of potential donors are maintained in many countries worldwide. Population-specific HLA characteristics determine the registry benefits for patients and also the need for further regional donor recruitment. In this work, we analyzed HLA allele and haplotype frequencies of donors of DKMS Chile, the first Chilean donor registry, with self-assessed “non-Indigenous” (n=92,788) and “Mapuche” (n=1,993) ancestry. We identified HLA alleles that were distinctly more abundant in the Chilean subpopulations than in worldwide reference populations, four of them particularly characteristic for the Mapuche subpopulation, namely B*39:09g, B*35:09, DRB1*04:07g, and DRB1*16:02g. Both population subsamples carried haplotypes of both Native American and European origin at high frequencies, reflecting Chile’s complex history of admixture and immigration. Matching probability analysis revealed limited benefits for Chilean patients (both non-Indigenous and Mapuche) from donor registries of non-Chilean donors, thus indicating a need for ongoing significant donor recruitment efforts in Chile.